Android Based Volleyball Passing Test Instrument Development Design - Destriana, Destriana; Destriani, Destriani; Victorian, Achmad Richard; Syariah, Syariah (Physical Education, Health and Recreation Study Program, Universitas Insan Budi Utomo, Indonesia, 2023)
This study aims to see how the design or design of an android-based volleyball passing test instrument. This study uses the Research and Development (Rnd) method using the ADDIE model. The ADDIE model is the Analysis phase, Design phase, Development phase, Implementation phase and Evaluation Phase. This research was carried out on July 17-20 September 2022. This research is only at the design stage, where at this design stage, it only displays concepts that are made systematically with the intention of making the product to be developed. The results of this study are that the product is designed using an appropriate test tool made with a laser and sensor installed in the test area then Arduino Mega as the brain or input and output controller of a circuit then added with NodeMCU can be used as a data sender so that it can be sent to the application that has been made. And downloaded on an Android-based cellphone, which was created with the help of the internet. Based on this design, it is hoped that it can be continued at the stage of developing an Android-based test instrument. This research is used as the basis for developing an android-based volleyball passing test instrument.